Literatur Review: Peran Analisis In Silico dalam Eksplorasi Senyawa Bioaktif Tanaman untuk Pengembangan Obat Antidiabetik - Fina Fatihatul Makia; Saeful Amin (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Diabetes mellitus (DM) is a major global health problem with a steadily increasing prevalence, posing significant impacts on both public health and the world economy. Conventional antidiabetic drugs such as metformin, sulfonylureas, and thiazolidinediones are effective in lowering blood glucose levels but have several limitations, including adverse effects and reduced efficacy with long-term use. Advances in medicinal chemistry and computational approaches such as molecular docking, quantitative structure activity relationship (QSAR), and virtual screening have opened new opportunities for discovering safer, more selective, and efficient antidiabetic agents. This literature review aims to explore the role of the in silico approach in identifying bioactive plant compounds as potential antidiabetic drug candidates. Based on the analysis of ten research articles, in silico methods have proven essential in predicting the affinity and stability of interactions between natural bioactive compounds and key protein targets involved in type 2 diabetes mellitus, including α-glucosidase, DPP-IV, PPAR-γ, PTP1B, Aldose Reductase, and SGLT-2. Compounds derived from plants such as Tinospora crispa (brotowali), Moringa oleifera (moringa), Syzygium polyanthum (bay leaf), mangosteen peel, Orthosiphon stamineus (cat’s whiskers), and Smallanthus sonchifolius (yacon) exhibited stronger binding affinities compared to synthetic reference drugs such as acarbose and alogliptin. Thus, the in silico approach based on medicinal chemistry serves as a crucial strategy to accelerate the discovery and development of multi-target antidiabetic phytopharmaceuticals derived from natural products. Despite the promising results, further in vitro, in vivo, and clinical studies are required to confirm the effectiveness, safety, and bioavailability of the identified compounds.